The burden of renal admissions in a tertiary Hospital in Sierra Leone - Joshua Coker; Onome Abiri; Obinna Jude Nwosu; Alhaji Gbla; Adetunji Wilson Taylor; Durodami Lisk (BMC Nephrology, 2022)
Abstract Background The burden of both acute kidney injury and chronic kidney disease is on the rise globally. In sierra Leone, there has been no data on renal patients or admissions. This study intends to close this gap in knowledge and give preliminary data on the burden of renal disease in this country. Methods The study was a retrospective review of the case notes of patients admitted at Connaught Hospital, Freetown over a 2 year period. Data extraction was done using a well- structured proforma. Results A 2.7% renal admission burden was obtained; mean duration of hospital stay was 15.1 ± 14.7; mean age of patients was 47.2 ± 17.5 with a female preponderance. The common risk factors for chronic kidney disease were systemic hypertension (43%) and diabetes mellitus (24%). The common risk factors for acute kidney injury were sepsis (77%) and hypovolemia (15%). The in- hospital mortality rate was 47% and 73% were non-compliant with haemodialysis probably due to financial reasons. Conclusion There is a significant burden of kidney disease in our environment, affecting mainly our young and middle-aged population. A rational approach is to embark on kidney disease prevention programs.